544 Two cases of constrictive pericarditis temporally associated with mRNA-1273 COVID-19 vaccination. (8th December 2021) - Diana, Davide; Cardillo, Ilaria; Polizzi, Vincenzo; Musumeci, Francesco
Abstract: Aims: The SARS-CoV-2 pandemic has led to the development of the mRNA vaccines in humans which are well tolerated, safe, and highly efficacious; however, post-marketing surveillance is revealing potential rare cardiac adverse effects as acute pericarditis. We herein report two cases of symptomatic constrictive pericarditis following administration of the second dose of mRNA-1273 (Moderna) SARS-CoV-2 vaccine. Methods and results: Case summary: A 75 years old male with history of hypertension and COPD presented to our Hospital approximately one month after the second dose of mRNA-1273 SARS-CoV-2 Vaccine with dyspnoea and leg oedema. Routine analysis resulted normal, no increasing of inflammatory markers or ECG abnormalities. Echocardiogram showed circumferential fibrinous pericardial effusion without tamponade and typical features of constrictive pericarditis: annulus reversus, ventricular interdependence, expiratory diastolic flow reversal in hepatic vein, inferior vena cava plethora. Pleural ultrasound showed bilateral pleural effusion that was sampled and showed a transudate fluid. Tumoral marker and a CT Scan, autoimmunity panel, blood tests for bacteraemia and Quantiferon were negative. Cardiac magnetic resonance imaging confirmed thickening of pericardium. A 68 years old male with history of ischaemic heart disease with previous CABG, hypertension, dyslipidaemia and chronic kidney disease presented with palpitations and mild legs swelling. Approximately, 2 months before he received the second dose of mRNA-1273 SARS-CoV-2 vaccine. Routine blood examinations resulted normal, ECG showed a right bundle branch block. Echocardiogram showed a mild enlargement of LV with normal systolic function, a moderate primary mitral regurgitation and a circumferential pericardial effusion, showing signs of constrictive syndrome. CT Scan demonstrated pericardium thickness. Constrictive pericarditis may represent a subacute complication of an asymptomatic exudative acute pericarditis. Although cases of acute pericarditis have been reported after SARS-CoV-2 vaccine, to our knowledge, the association with constrictive pericarditis has not been described. The temporal link between vaccination and symptoms development as the biological plausibility of autoimmune or cross-reaction response to vaccination in predisposed subjects could suggest a possible correlation as an adverse event, even if causality could not be established. Conclusions: We present two cases of constrictive pericarditis occurring after mRNA-1273 SARS-CoV-2 vaccination, aiming further data to confirm a causal role.